-4(2x-3)=-8x+5
Hi Cheryl!
The first thing you have to do with this is multiply the -4 into the stuff in the parenthesis.
-4*2x = -8x
-4*-3 = +12
So the left side is -8x+12 = -8x +5
Now that I'm this far along, we see that there's no real answer to this. If we add -8x to both sides, we get:
12=5. And that's clearly wrong.
Either the book/paper/whatever made a mistake in typing this or they are trying to show this question won't work.
So this was a very good question to put up here because it simply doesn't work. Since you had trouble with it, it looks like you probably did it correctly ;-)